Bovine Bodies and Foreign Kings: Immunity and Dharma in the Hindu Epics - Newman, Adam Lee (History of religions, 2025)
This article explores a brief but rhetorically powerful interaction between Vasiṣṭha and Viśvāmitra found in the two Sanskrit Hindu narratives Mahābhārata and Rāmāyaṇa. The story involves the emission of non-Āryan, non-Brahminical forest-dwelling and foreign groups from the Brahminically pure body of the wish-granting cow (kāmadhenu/surabhī) and explores one possible meaning for this rather perplexing narrative moment. I draw upon the metaphor of biopolitical immunity as explored by Roberto Esposito, particularly in his Immunitas: The Protection and Negation of Life, to help understand the narrative emission of non-Āryan bodies from the body of the wish-granting cow and her destruction of Viśvāmitra’s army. In short, the king Viśvāmitra trespasses into Brahminical space, at which point he is perceived as a threat and becomes, as it were, akin to a contagion. What I suggest in this article is that the wish-granting cow emits non-Āryan groups from her divine body as an immunitary response to the trespassing of Viśvāmitra and his violent army into the domain of the Brahmin. The armies that the wish-granting cow emits are a threat to the Brahminical body politic but are included within the domain of the political body in order to minimize and circumscribe their threat.